Tolerogenic Effect Elicited by Protein Fraction Derived From Different Formulas for Dietary Treatment of Cow’s Milk Allergy in Human Cells - Paparo, Lorella; Picariello, Gianluca; Bruno, Cristina; Pisapia, Laura; Canale, Valentina; Sarracino, Antonietta; Nocerino, Rita; Carucci, Laura; Cosenza, Linda; Cozzolino, Tommaso; Berni Canani, Roberto (Frontiers in Immunology, 2021)
Several formulas are available for the dietary treatment of cow’s milk allergy (CMA). Clinical data suggest potential different effect on immune tolerance elicited by these formulas. We aimed to comparatively evaluate the tolerogenic effect elicited by the protein fraction of different formulas available for the dietary treatment of CMA. Five formulas were compared: extensively hydrolyzed whey formula (EHWF), extensively hydrolyzed casein formula (EHCF), hydrolyzed rice formula (HRF), soy formula (SF), and amino acid-based formula (AAF). Formulas were reconstituted in water according to manufacturer’s instructions, and subjected to an in vitro infant gut simulated digestion using a sequential gastric and duodenal static model. Protein fraction was then purified, and used for the experiments on non-immune and immune components of tolerance network in human enterocytes and in peripheral mononuclear blood cells (PBMCs). We assessed epithelial layer permeability and tight junction proteins (occludin and zonula occludens 1, ZO-1), mucin 5AC, IL-33 and thymic stromal lymphopoietin (TSLP) in human enterocytes. In addition, Th1/Th2 cytokines response and Treg activation were investigated in PBMCs from IgE-mediated CMA infants. EHCF-derived protein fraction positively modulated the expression of gut barrier components (mucin 5AC, occludin and ZO-1) in human enterocytes, while SF was able to stimulate the expression of occludin only. EHWF and HRF protein fractions elicited a significant increase in TSLP production, while IL-33 release was significantly increased by HRF and SF protein fractions in human enterocytes. Only EHCF-derived protein fraction elicited an increase of the tolerogenic cytokines production (IL-10, IFN-γ) and of activated CD4+FoxP3+ Tregs number, through NFAT, AP1 and Nf-Kb1 pathway. The effect paralleled with an up-regulation of FoxP3 demethylation rate. Protein fraction from all study formulas was unable to induce Th2 cytokines production. The results suggest a different regulatory action on tolerogenic mechanisms elicited by protein fraction from different formulas commonly used for CMA management. EHCF-derived protein fraction was able to elicit tolerogenic effect through at least in part an epigenetic modulation of FoxP3 gene. These results could explain the different clinical effects observed on immune tolerance acquisition in CMA patients and on allergy prevention in children at risk for atopy observed using EHCF.